Comment on the article by J. Elgeti, U. B. Kaupp, and G. Gompper: hydrodynamics of sperm cells near surfaces. - Smith, D; Gaffney, E; Shum, H; Gadêlha, H; Kirkman-Brown, J (2011)
A recent study by Elgeti et al. used multiparticle collision dynamics to simulate a long-standing problem: the approach of sperm to surfaces, and subsequent accumulation. The authors highlight differences in their predictions with those of the earlier Stokes flow simulations of Smith et al. attributing the differences to methodological flaws in the earlier article. In this Comment, we discuss the criticisms leveled in detail, and review some recently published work that shows how species-specific details of cell morphology provides a more likely explanation for the differing predictions of the two studies. We also highlight experimental work that supports the study of Smith et al.